Wear behavior of gas tungsten arc deposited FeCrC, FeCrSi, and WCo coatings on AISI 1018 steel - Yilmaz, SO (Elsevier Science Sa, 2005)
FeCrC, FeCrSi, and Wo alloy powders were used to deposit coatings on a low-carbon AISI 1018 steel substrate by gas tungsten arc processing (GTA). This method is an easy and effective technique in producing a hard layer with a thickness of about 2-4 min and hardness between 700 and 950 HV Depending on the processing parameters and powder type, either hypoeutectic or hypereutectic microstructures were obtained in coated surfaces. Martensitic, and martensite+pearlitic structures were formed at the interface between the coating and substrate. The friction and the wear behavior of the coated surfaces were evaluated under dry sliding conditions, with a WCo coating used as a reference coated surface. The dry sliding wear tests were performed on a pin on disc machine. The wear rates of the tests were affected by the applied load. Additionally, between wear rates and thermal conductivities correlations were detected. Among the FeCrC, FeCrSi and Wo coated surfaces, it was seen that the surface coated with FeCrC powders showed the best wear resistance. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: GTA; dry sliding vear; surface coating